1988
DOI: 10.1159/000215824
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen: A Brief Introduction into Its Biochemistry and Function

Abstract: Human plasminogen is a β-globulin (2 % carbohydrate, molecular weight 90 KD), which in its native form has NH2-terminal glutamic acid (Glu-plasminogen) whose primary structure is known (31, 37, 38). From human plasma plasminogen can easily be isolated by affinity chromatography techniques (10, 25, and Table 1). Plasminogen is synthesized in many organs. The production site of the zymogen may be the liver (21), the eosinophiles (3) or the kindney (15). The plasma-plasminogen level is low in newborns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…Flow cytometric analyses have shown that all three receptors are present at the meningococcal surface, but at low levels. However, it is well known from other bacterial pathogens that plasminogen receptors can be present at the cell surface at very low levels, as plasminogen is highly abundant in many body fluids (serum concentrations, ϳ1.6 to 2 mol/liter, roughly corresponding to 100 to 200 mg/liter) (2,12,35,39). The presence of pneumococcal enolase, which has been shown to act as the major plasminogen receptor of S. pneumoniae, at the surfaces of these bacteria has been studied in detail (29).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analyses have shown that all three receptors are present at the meningococcal surface, but at low levels. However, it is well known from other bacterial pathogens that plasminogen receptors can be present at the cell surface at very low levels, as plasminogen is highly abundant in many body fluids (serum concentrations, ϳ1.6 to 2 mol/liter, roughly corresponding to 100 to 200 mg/liter) (2,12,35,39). The presence of pneumococcal enolase, which has been shown to act as the major plasminogen receptor of S. pneumoniae, at the surfaces of these bacteria has been studied in detail (29).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this binding is inhibitable in the presence of the lysine analogue tranexamic acid (Fig. 1J) indicates that plasminogen interacts with the surface of B. burgdorferi via its lysine-binding sites (27).…”
Section: Resultsmentioning
confidence: 98%
“…The mobilities of the ␣Ј-and ␤-chains of the intact C3b protein are shown in lane 1. In the presence of ⑀ACA, aprotinin, or ␣ 2 -antiplasmin (␣2-AP), C3b cleavage was reduced (lanes [3][4][5]. Cleavage products generated by the complement serine protease Factor I in the presence of a cofactor (Factor H) were identified as ␣Ј68, ␣Ј43, and ␣Ј41 (lane 6).…”
Section: ␤-Chainsmentioning
confidence: 99%